Affective computing - Picard, Rosalind W. (Cambridge, Mass. : MIT, 2000)
pt. 1. Envisioning affective computing ## ch. 1. Emotions are physical and cognitive ## ch. 2. Affective computers ## ch. 3. Applications of affective computing ## ch. 4. Potential concerns ## ## pt. 2. Building affective computing ## ch. 5. Affective signals and systems ## ch. 6. Recognizing and expressing affect ## ch. 7. Emotion synthesis ## ch. 8. Affective wearables.
boek